Implementation of learning reading and writing activities for 5th class students - La Rabani; Mansyur M (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The school literacy movement is a social movement that combines various components. The government has launched that schools carry out reading and writing learning activities as a